2016
DOI: 10.5194/gmd-2016-58
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient urban canopy parametrization for atmospheric modelling: description and application with the COSMO-CLM model (version 5.0_clm6) for a Belgian Summer

Abstract: Abstract. This paper presents the Semi-empirical URban-canopY parametrization SURY, which bridges the gap between bulk urban land-surface schemes and explicit-canyon schemes. Based on detailed observational studies, modelling experiments and available parameter inventories, it offers a robust translation of urban canopy parameters containing the three-dimensional information into bulk parameters. It is extremely suitable for an intrinsic representation of canopy-dependent urban physics in existing bulk urban l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 89 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…Their results conclude that changes in land‐surface properties (hydrothermal or geometric) have a significant impact on the evolution of the overlying boundary layer. In addition, Wouters et al (2016) tested urban canopy parameter value ranges from the Local Climate Zones (Stewart and Oke, 2012) in an online simulation over the Belgian territory with COSMO‐CLM coupled to TERRA_URB. Their study, amongst other results, reveals that, with respect to surface temperatures, air temperatures and associated urban heat islands, one should prioritize those parameters that are most sensitive: the thermal parameters and the anthropogenic heat emissions.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Their results conclude that changes in land‐surface properties (hydrothermal or geometric) have a significant impact on the evolution of the overlying boundary layer. In addition, Wouters et al (2016) tested urban canopy parameter value ranges from the Local Climate Zones (Stewart and Oke, 2012) in an online simulation over the Belgian territory with COSMO‐CLM coupled to TERRA_URB. Their study, amongst other results, reveals that, with respect to surface temperatures, air temperatures and associated urban heat islands, one should prioritize those parameters that are most sensitive: the thermal parameters and the anthropogenic heat emissions.…”
Section: Introductionmentioning
confidence: 83%
“…TERRA_URB (Wouters et al , 2015, 2016) is the bulk urban land‐surface scheme of the COSMO(‐CLM) model. It represents the variability of ground heat and moisture transport, the turbulent transfer of momentum, heat and moisture, and the surface–atmosphere radiative exchanges in urban areas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main benefit of applying default parameter values is an easy transfer of the CER to other cities. Wouters et al () also detected that the sensitivity of T 2 and surface temperature to parameter values is lower than the sensitivity to different UCMs when using the COSMO‐CLM model. While some former studies (Kim et al , ; Fallmann et al , ; Shaffer et al , ) also revealed no improvements with increasing complexity, other studies (Kusaka et al , ; Kim et al , ; Li and Bou‐Zeid, ) detected that more complex schemes (SLUCMs or multi‐layer UCMs) perform better than slab models.…”
Section: Discussionmentioning
confidence: 99%